Deaths and accidents: Analysis of deaths from occupational accidents in Brazil from 2012 to 2019 - Silva , José Thiago de Lima; Santos, Isadora Sabrina Ferreira dos; Silva, Maria Luiza Ferreira Imburana da; Barreto, Isabel Brandão de Jesus; Rodrigues, Barbara Leticia Silvestre; Oliveira, Emília Carolle Azevedo de (Seven Editora, 2023)
Introduction: Work accidents are a major public health problem, Brazil occupies the fourth place in the  world ranking of fatal work accidents. It is estimated that there are about 318 thousand deaths in the world, caused by occupational accidents, as well as 2 million diseases related to accidents. Objective: To analyze deaths from occupational accidents recorded in Brazil, identifying and describing their epidemiological profile from 2012 to 2019. Method: Cross-sectional epidemiological study of deaths from occupational accidents recorded in the Mortality Information System (SIM) of Brazil, from 2012 to 2019, analyzed in Microsoft Excel 2019® and the R 4.0.2 software. Results: There were 27,510 deaths due to occupational accidents, with a decreasing trend in the mortality rate; most of which  occurred in the Southeast region (33.44%), in males (94.27%), in the age group between 30-39 years (24.06%), whites (49.43%), schooling (29.92%) of the individuals who evolved to death had from 8 to 11 studies, regarding the place of occurrence of occupational accidents (33.73%) of the deaths occurred in the hospital. Conclusion: It is evident the need for surveillance actions in workers' health, training, continuous training and public policies to cope with social determinants and conditioning, with the objective of reducing occupational accidents and consequently deaths. DOI:https://doi.org/10.56238/innovhealthknow-003